Transcriptome profiling disclosed the effect of single and combined drought and heat stress on reprogramming of genes expression in barley flag leaf - Mikołajczak, Krzysztof; Kuczyńska, Anetta; Krajewski, Paweł; Kempa, Michał; Nuc, Maria (Frontiers in Plant Science, 2023)
Despite numerous studies aimed to unravel the genetic background of barley response to abiotic stress, the transcriptome modulation induced by combinatorial drought and increased temperature remains largely unrecognized. Very limited studies were done especially on the flag leaf playing important role in grain filling in cereals. In the present study, transcriptome profiles along with chlorophyll fluorescence parameters and yield components were compared between barley genotypes with different flag leaf size under single and combined drought and heat stress. High-throughput mRNA sequencing revealed 2,457 differentially expressed genes which were functionally interpreted using Gene Ontology term enrichment analysis. The transcriptomic signature under double stress was more similar to effects caused by drought than by elevated temperature; it was also manifested at phenotypic and chlorophyll fluorescence levels. Both common and stress-specific changes of transcripts abundance were identified. Genes regulated commonly across stress treatments, determining universal stress response, were associated, among others, with response to drought, heat, and oxidative stress. In addition, changes specific to the size of the flag leaf blade were found. Our study allowed to identify sets of genes assigned to various processes underlying response to drought and heat, including photosynthesis, abscisic acid pathway or lipid transport. Genes encoding LEA proteins including dehydrins, and heat shock proteins were especially induced by stress treatments. Some association between genetic composition and flag leaf size was confirmed, on the other hand there was no general coincidence between SNP polymorphism of genotypes and differential expression of genes induced by stress factors. This research provided novel insight into molecular mechanisms of barley flag leaf that determine drought and heat response, also during their co-occurrence.